Instationary metabolic flux analysis reveals that NPC1 inhibition increases glycolysis and decreases mitochondrial metabolism in brain microvascular endothelial cells - Bilal Moiz; Matthew Walls; Viviana Alpizar Vargas; Anirudh Addepalli; Callie Weber; Andrew Li; Ganesh Sriram; Alisa Morss Clyne (Neurobiology of Disease)
Niemann Pick Disease Type C (NP-C), a rare neurogenetic disease with no known cure, is caused by mutations in the cholesterol trafficking protein NPC1. Brain microvascular endothelial cells (BMEC) are thought to play a critical role in the pathogenesis of several neurodegenerative diseases; however, little is known about how these cells are altered in NP-C. In this study, we investigated how NPC1 inhibition perturbs BMEC metabolism in human induced pluripotent stem cell-derived BMEC (hiBMEC). We incorporated extracellular metabolite and isotope labeling data into an instationary metabolic flux analysis (INST-MFA) model to estimate intracellular metabolic fluxes. We found that NPC1 inhibition significantly increased glycolysis and pentose phosphate pathway flux while decreasing mitochondrial metabolism. These changes may have been driven by gene expression changes due to increased cholesterol biosynthesis, in addition to mitochondrial cholesterol accumulation. We corroborated these findings in primary BMEC, an alternative in vitro human brain endothelial model. Finally, we found that co-treatment with hydroxypropyl-β cyclodextrin (HPβCD) partially restored metabolic phenotype in U18666A-treated BMECs, suggesting that this drug may have therapeutic effects on the brain endothelium in NP-C. Together, our data highlight the importance of NPC1 in BMEC metabolism and implicate brain endothelial dysfunction in NP-C pathogenesis.